Variété inclusive et vérité morphologique : petite typologie des noms communs de personne abrégés - Daniel Elmiger (Glad!)
For some years now, abbreviations of French personal nouns have been multiplying in usage, and there is a rich variety of formal realisations (different cuts, different abbreviation signs, etc.). Several issues related to abbreviated common nouns are thematized and exemplified, in particular with the help of the designation « collaborateur(s) / collaboratrice(s) », which presents several morphological particularities. The result is a rich panoply of forms and functions, which testifies to the complexity of the phenomenon in French.